Characterization of water management in metal foam flow-field based polymer electrolyte fuel cells using in-operando neutron radiography. (13th January 2020) - Wu, Y.; Cho, J.I.S.; Whiteley, M.; Rasha, L.; Neville, T.P.; Ziesche, R.; Xu, R.; Owen, R.; Kulkarni, N.; Hack, J.; Maier, M.; Kardjilov, N.; et al.
Abstract: Metal foam flow-fields have shown great potential in improving the uniformity of reactant distribution in polymer electrolyte fuel cells (PEFCs) by eliminating the 'land/channel' geometry of conventional designs. However, a detailed understanding of the water management in operational metal foam flow-field based PEFCs is limited. This study aims to provide the first clear evidence of how and where water is generated, accumulated and removed in the metal foam flow-field based PEFCs using in-operando neutron radiography, and correlate the water 'maps' with electrochemical performance and durability. Results show that the metal foam flow-field based PEFC has greater tolerance to dehydration at 1000 mA cm −2, exhibiting a ~50% increase in voltage, ~127% increase in total water mass and ~38% decrease in high frequency resistance (HFR) than serpentine flow-field design. Additionally, the metal foam flow-field promotes more uniform water distribution where the standard deviation of the liquid water thickness distribution across the entire cell active area is almost half that of the serpentine. These superior characteristics of metal foam flow-field result in greater than twice the maximum power density over serpentine flow-field. Results suggest that optimizing fuel cell operating condition and foam microstructure would partly mitigate flooding in the metal foam flow-field based PEFC. Graphical abstract: Image 1 Highlights: Neutron imaging applied to water management in metal foam flow-field based PEFC. The metal foam flow-field enhances the uniformity of water distribution. The metal foam flow-field improves the tolerance to dehydration. The metal foam flow-field is susceptible to flooding at low current density.